Package of menthol measures for thirst relief: a randomized clinical study - Viviane Moreira Serato; Lígia Fahl Fonseca; Marcela Maria Birolim; Edilaine Giovanini Rossetto; Lílian Denise Mai; Aline Korki Arrabal Garcia
ABSTRACT Objective: To evaluate the effectiveness of the menthol package (lip hydration and ice popsicles) compared to a package of non-menthol measures (lip hydration and ice popsicles) as a way to relieve thirst in patients in the Anesthetic Recovery Room. Method: Randomized and parallel trial study, with 120 patients randomized patients in an experimental group - menthol measurements (n=59) and control group - measures without menthol (n = 61). Results: There was a significant (p<0.05) decrease in intensity, hydration, dryness and taste in the oral cavity between the three moments of assessment/intervention in the two groups. The difference was significant in the experimental group for thirst intensity at the second assessment/intervention point (p<0.05) after a single administration of the menthol package. Conclusion: There was a reduction in thirst intensity in both groups. Patients who received menthol packages showed a significant decrease in intensity after a single evaluation/intervention time. NCT: 02869139.